Sustainable Development: Assessing the Role of Corporate and Private Sector Organizations in Southwest, Nigeria: A Case Study - AROGE, Israel Olabode; AROGE, Iyinoluwa Paul (ABUAD Journal of Engineering and Applied Sciences, 2025)
This study critically examined the role of corporate and private sector entities in fostering sustainable development in Southwest Nigeria, with a particular focus on empowering local communities. Utilising a mixed-methods approach—comprising descriptive and inferential statistics, including One-Way ANOVA, alongside semi-structured interviews—the research drew on 355 valid responses from 400 distributed questionnaires (88.8% response rate) spanning diverse professional sectors. Findings revealed a significant disconnect between corporate initiatives and the actual developmental needs of local communities. While previous scholars have emphasised the importance of partnerships and corporate social responsibility, this study advances practical, actionable recommendations. These include the institutionalisation of community-based co-design frameworks where corporations co-create development projects with local stakeholders from inception to implementation. Additionally, the study recommends the establishment of Local Development Accountability Councils (LDACs) comprising corporate representatives, community leaders, and civil society actors to ensure transparency, continuous dialogue, and contextualised impact measurement. Businesses should integrate sustainability into their core operational strategies through mandatory Environmental, Social, and Governance (ESG) compliance reporting at regional levels. Moreover, the government should incentivise private sector involvement via tax reliefs, competitive grants, and access to land or infrastructure for community-oriented projects. The study provides a novel metrics toolkit for measuring corporate-community impact tailored to the socio-economic realities of the region. Overall, the research offers deeper insights for policymakers, corporate leaders, development practitioners, and researchers seeking to align profit-driven goals with inclusive and sustainable growth in the Southwest, Nigeria.